New pharmacotherapeutic approaches for the treatment of peripheral T-cell lymphoma - M. А. Sorokina; A. V. Rakhteenko; T. R. Grishina (Фармакоэкономика, 2023)
Today, it is difficult to overestimate the new directions in the pharmacotherapy of peripheral T-cell lymphomas (PTCL): immunotherapy, including adoptive, targeted therapy and chemotherapy. However, there are few biomarkers that predict response to therapy. A big problem is patients with refractory and recurrent PTCL who do not respond to such therapy or demonstrate adverse events, which makes it important to personalize therapy and search for predictive markers, followed by thorough analytical and clinical validation. The literature highlights the importance of using biomarkers obtained from whole exome sequencing and tumor transcriptome sequencing. The review discusses the T cell ontogenesis, as well as the possibilities of personalization of anticancer drugs such as azacitidine, duvelisib, romidepsin, and bortezomib for the treatment of refractory or recurrent PTCL.